Transplantation Outcomes in Primary Hyperoxaluria - Bergstralh, Eric J. (2010)
Optimal transplantation strategies are uncertain in primary hyperoxaluria (PH) due to potential for recurrent oxalosis. Outcomes of different transplantation approaches were compared using life table methods to determine kidney graft survival among 203 patients in the International Primary Hyperoxaluria Registry. From 1976–2009, 84 kidney alone (K) and combined kidney and liver (K+L) transplants were performed in 58 patients. Among 58 first kidney transplants (32 K, 26 K+L), 1, 3, and 5 year kidney graft survival was 82%, 68%, and 49%. Renal graft loss occurred in 26 first transplants due to oxalosis in 10, chronic allograft nephropathy in 6, rejection in 5, and other causes in 5. Delay in PH diagnosis until after transplant favored early graft loss (p=0.07). K+L had better kidney graft outcomes than K with death censored graft survival 95% vs. 56% at 3yrs (p=.011). Among 29 year 2000–09 first transplants (24 K+L), 84% were functioning at 3 years compared to 55% of earlier transplants (p=0.05). At 6.8 years after transplantation, 46 of 58 patients are living (43 with functioning grafts). Outcomes of transplantation in PH have improved over time, with recent K+L transplantation highly successful. Recurrent oxalosis accounted for a minority of kidney graft losses.